Crystal structure and luminescence properties of a single‐component white‐light‐emitting phosphor Ca8ZnLa(PO4)7:Eu2+, Mn2+. Issue 7 (10th April 2017) - Mi, Ruiyu; Liu, Yan‐gai; Mei, Lefu; Zhao, Chenglong; Chen, Jian; Huang, Zhaohui; Fang, Minghao
Abstract: A series of novel green emission Whitlockite‐type Ca8 ZnLa(PO4 )7 :Eu 2+ and color tunable Ca8 ZnLa(PO4 )7 :Eu 2+, Mn 2+ phosphors were prepared by the solid‐state reaction method in a reducing atmosphere. Its crystal structure and phase composition were identified by high‐resolution transmission electron microscopy, selected area electronic diffraction, X‐ray photoelectron spectroscopy, and X‐ray powder diffraction Rietveld refinement, and it was found to be trigonal, belonging to R ‐3 c (161) space group. The luminescence properties of Eu 2+ singly doped and Eu 2+ /Mn 2+ codoped Ca8 ZnLa(PO4 )7 phosphors were revealed in detail. Ca8 ZnLa(PO4 )7 :Eu 2+ is excitable over a broad range from 200 to 450 nm with a prominent green emitting. With varied Eu 2+ /Mn 2+ ratios, fine‐tune emission under 365 nm excitation can be achieved from green (0.221, 0.468) to magenta (0.391, 0.276), especially the warm white light (0.392, 0.352), and CCT 3500 K can be obtained by the process of energy transfer between Eu 2+ and Mn 2+ . The ET mechanism in this system is managed via the dipole‐dipole interaction with the maximum energy‐transfer efficiency 82.8% based on the decay lifetime data. These results suggest that as‐prepared phosphors can serve as promising candidates of UV‐pumped w‐ LEDs.